Socioeconomic factors related to the divorce rate of woman in Peru - Castillo Chiroque, Antony Raul Stuardo (2021)
Objective: To determine the relationship between socioeconomic factors and the divorce rate of women in the departments of Peru. Method: The research was quantitative, non-experimental and cross-sectional; descriptive, correlational and explanatory in scope. The population was seized from the macroeconomic data of the women of Peru’s 24 departments, data that was obtained from the statistical series of the XII Population Census, VII Housing and III Indigenous Communities or Peruvian Census of 2017. Results: Divorce rate and the female workforce with higher education have a strong positive correlation of 74.80%; Divorce rate and head of household with high purchasing power presented a direct and significant correlation of 96.8%; Divorce rate and urbanity presented a direct and positive correlation of 64.70%. Conclusion: The divorce rate has a high direct and significant correlation with the female labor force, with purchasing power, and urbanity.